2010
DOI: 10.1016/j.exer.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Corneal myofibroblast generation from bone marrow-derived cells

Abstract: The purpose of this study was to determine whether bone marrow-derived cells can differentiate into myofibroblasts, as defined by alpha smooth muscle actin (SMA) expression, that arise in the corneal stroma after irregular phototherapeutic keratectomy and whose presence within the cornea is associated with corneal stromal haze. C57BL/6J-GFP chimeric mice were generated through bone marrow transplantation from donor mice that expressed enhanced green fluorescent protein (GFP) in a high proportion of their bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 16 publications
2
113
0
3
Order By: Relevance
“…38 Currently, it is unclear what percentage of myofibroblasts is of bone marrow cell origin during in vivo corneal wounding. In our study, all myofibroblasts were derived from corneal fibroblasts, and it is unknown whether myofibroblasts of differing origins will respond in a similar manner to micro-and nanoscale topographic cues.…”
Section: Substratum Topography Stabilizes the Corneal Fibroblast Phenmentioning
confidence: 99%
“…38 Currently, it is unclear what percentage of myofibroblasts is of bone marrow cell origin during in vivo corneal wounding. In our study, all myofibroblasts were derived from corneal fibroblasts, and it is unknown whether myofibroblasts of differing origins will respond in a similar manner to micro-and nanoscale topographic cues.…”
Section: Substratum Topography Stabilizes the Corneal Fibroblast Phenmentioning
confidence: 99%
“…52 This may have important implications for devising new treatments to prevent haze and may also provide a biological explanation for the cellular difference in humans between steroid-responsive haze and steroid-unresponsive haze. Our working hypothesis is that the myofibroblasts in steroid-responsive haze are primarily derived from bone marrow-derived cells and, therefore, retain the capacity to undergo cell death in response to corticosteroids.…”
Section: Wound Healing and Myofibroblasts After Surface Ablationmentioning
confidence: 99%
“…26,50,51,62 Scattering light more intensely than quiescent keratocytes and producing large amounts of disorganized extracellular matrix, myofibroblasts play an important role in corneal haze. 72 Recently, Barbosa et al 52 have shown in a chimeric mouse model that bone marrow-derived cells can differentiate into corneal stromal myofibroblasts associated with haze after phototherapeutic keratectomy (PTK).…”
Section: As Adjuvant Therapy After Prkmentioning
confidence: 99%
See 1 more Smart Citation
“…Non fibroblastic cell lineages [27][28][29] can differentiate into myofibroblasts through the processes of epithelial-mesenchymal transition [30] and endothelial-mesenchymal transition [31]. MSCs are myofibroblast precursors in several pathological states [32]. An important particular case is the presence of myofibroblasts in normal human placenta, a tissue in which the population of contractile myofibroblasts is dominant in placental stem villi [33].…”
Section: Generalmentioning
confidence: 99%